Ditransitive and dative constructions in English and Thai languages - Anongnad Petchprasert, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article presents predominant views of the English and Thai ditransitive and dative sentence structures that take verbs to have two major meanings based on schemata: a caused possession and a caused motion. The main purpose of the study was to investigate the associations between verbs and their event schemata, the syntactic and semantic realizations available to the ditransitive and dative sentence structures, and the associations between the parallel structures of the sentences across the languages. The participants of the study were pre-service teachers majoring in English at a university in Thailand. The study was conducted in the 2020 academic year. The analyses demonstrated inference patterns and verb arguments in the double object construction across English and Thai. The results of the study also identified the syntactic and semantic similarities and differences with an account of variant choices that provided insightful explanations of the data in the crosslinguistic realm. Implications for educators revolve around individual differences and other related variables that might yield various results. The findings also suggest the multidimensionality of research into the crosslinguistic analyses of double object construction and linguistic devices.